PENINGKATAN PENGENALAN BUDAYA DAERAH MELALUI PERMAINAN TRADISIONAL PADA ANAK USIA DINI - Retno Istriningsih; Nur Halizah; Puji Astuti; Dwi Sugiarti; Dwi Prasetiyawati Diyah Hariyanti (Universitas Muhammadiyah Metro, 2026)
Introducing regional culture in early childhood is important for developing children’s character and cultural identity. However, the rapid growth of digital technology has caused children to become more familiar with popular culture than local culture. This study aimed to improve early childhood children’s ability to recognize regional culture through traditional games. The study employed Classroom Action Research (CAR) using the Kemmis and McTaggart model conducted in two cycles consisting of planning, implementation, observation, and reflection stages. The participants were 10 children of Group B at KB Ceria Sendangdawung Village. Data were collected through observation, interviews, and documentation. Data analysis used qualitative and quantitative descriptive approaches. The results showed a significant improvement in children’s ability to recognize regional culture. In the pre-cycle stage, 80% of children were categorized as “Not Yet Developed.” In Cycle I, 40% of children reached the “Developing as Expected” category and 10% reached the “Very Well Developed” category. The most significant improvement occurred in Cycle II, where 80% of children achieved the “Very Well Developed” category. Traditional games proved effective in improving children’s understanding of regional culture, local language use, and participation in learning activities.